2020
DOI: 10.3389/fpls.2020.00326
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Control of Reproductive Traits in Tomatoes Under High Temperature

Abstract: Global climate change is increasing the range of temperatures that crop plants must face during their life cycle, giving negative effects to yields. In this changing scenario, understanding the genetic control of plant responses to a range of increasing temperature conditions is a prerequisite to developing cultivars with increased resilience. The current work reports the identification of Quantitative Trait Loci (QTL) involved in reproductive traits affected by temperature, such as the flower number (FLN) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 54 publications
(89 reference statements)
11
45
0
Order By: Relevance
“…Recently, the role of plasma membrane-associated ATPases in maintaining plant fertility was reported as these transporters control the ion balance by controlling downstream pH-dependent mechanisms essential for pollen tube growth ( Hoffmann et al, 2020 ). Thus, based on our analysis and previous reports, we suggest that the downregulation of key genes involved in transmembrane transport is one of the key reasons for the loss of pollen function under heat stress conditions ( Frank et al, 2009 ; Giorno et al, 2010 ; Fragkostefanakis et al, 2016 ; Keller et al, 2018 ; Gonzalo et al, 2020 ).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Recently, the role of plasma membrane-associated ATPases in maintaining plant fertility was reported as these transporters control the ion balance by controlling downstream pH-dependent mechanisms essential for pollen tube growth ( Hoffmann et al, 2020 ). Thus, based on our analysis and previous reports, we suggest that the downregulation of key genes involved in transmembrane transport is one of the key reasons for the loss of pollen function under heat stress conditions ( Frank et al, 2009 ; Giorno et al, 2010 ; Fragkostefanakis et al, 2016 ; Keller et al, 2018 ; Gonzalo et al, 2020 ).…”
Section: Resultssupporting
confidence: 72%
“…While high temperature is expected to affect male and female reproductive tissues concurrently, the available data mainly focusses on the effects of heat stress on pollen development and function. Nevertheless, there is a recent focus on the female reproductive organ sensitivity to high temperature in crops like sorghum, rice, maize, wheat, and tomato ( Gonzalo et al, 2020 ; Jagadish, 2020 ; Lohani et al, 2020b ). The outcomes of these studies reveal a considerable variation in heat stress response of pistil (stigma or ovary) across crops.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the wild tomato species usually show high pollen viability and pollen number even under heat stress conditions [ 37 ]. Moreover, it has been demonstrated that some accessions of S. pimpinellifolium exhibit a good level of thermotolerance [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that two QTLs carrying a S. pimpinellifolium allele and mapping on chromosomes 2 and 4 affect the number of flowers in tomatoes [ 41 ]. Moreover, very recently, a QTL displaying a consistent effect on NFL and TNF was located on the distal region of chromosome 2 in a set of RILs and ILs deriving from a cross between S. lycopersicum and S. pimpinellifolium [ 38 ]. In the present study, we found SNPs and InDels in these same regions, which are currently being investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The phytaspase 2 coding gene, Solyc04g078740, segregating for an SNP in the RIL population, was found as a candidate gene (and at the QTL peak) for both FlN_C_4 and FlN_WD_4.1 ( Table 2 and Table S5 ). Two QTLs for the number of flowers under high temperatures fln4.1_T2_2E and fln4.1_T3_2E were reported in a similar genetic position using a different RIL population [ 58 ]. Other genes related to the peptide signaling pathway were found within QTL clusters III, VIII, X, and V ( Table 3 and Table S5 ) and cytokinin QTLs ZR_WD_4 (Solyc04g077170), and ZR_WD_10 (Solyc10g011830).…”
Section: Discussionmentioning
confidence: 99%